(untitled) (Comparative & International Education Series, 2021)
The role of the institution in students’ decisions about study abroad participation is currently an under-explored topic in international education research. While recent research has identified myriad factors, such as demographic characteristics, students’ beliefs, and elements of their social and cultural capitals before and during college, as they relate to study abroad, very little attention has been given to how the type of institution that a student attends relates to study abroad participation. This study focuses on the relationship between research institution attendance and both study abroad participation and, among participants, location and duration of study abroad. In this way, this study speaks to both variations in study abroad participation itself and variations in students’ study abroad experiences, as related to research institution attendance. Using data from the University System of Georgia, the relationship between research institution attendance and study abroad participation was estimated in two different ways, the first using standard regression techniques and the second using propensity score weighting. This latter technique balanced data based on pre-college-enrollment characteristics. Analyses predicting location and duration of study abroad likewise used propensity score modeling. Results indicated a significant, negative relationship between enrollment at a research institution and study abroad, a finding that is possibly explained by variations in students’ major fields of study. In contrast, findings related to location and duration of study abroad suggested a stratification of opportunity in study abroad experiences related to research institution attendance. Specifically, this study’s findings indicated that students enrolled at research institutions participated in longer study abroad programs in more varied locations compared to their non-research-institution counterparts. Taken together, these findings suggest that while study abroad may be accessible at both research and non-research institutions, students’ study abroad experiences are stratified along the lines of institution type.